1/2 - (5/8)x = (7/8)x + 7/2

1/2 = (12/8)x + 7/2 (add 5/8x to both sides)

-6/2 = (3/2)x (subtract 7/2 from both sides)

(-6/2)(2/3) = x = -2 (multiply both sides by 2/3)

Check

1/2 -5/8(-2) = 7/8(-2) +7/2

1/2 +5/4 = -7/4 +7/2

7/4 = 7/4 (x=-2 satisfies the equation)

1/2 = (12/8)x + 7/2 (add 5/8x to both sides)

-6/2 = (3/2)x (subtract 7/2 from both sides)

(-6/2)(2/3) = x = -2 (multiply both sides by 2/3)

Check

1/2 -5/8(-2) = 7/8(-2) +7/2

1/2 +5/4 = -7/4 +7/2

7/4 = 7/4 (x=-2 satisfies the equation)